The Effects of Fiscal Policy in New Zealand: Evidence from a VAR Model with Debt Constraints - Oscar Parkyn; Tugrul Vehbi (New Zealand Government, The Treasury, 2013)
This paper investigates the macroeconomic effects of fiscal policy in New Zealand using a structural Vector Autoregression (SVAR) model. The model is the five-variable structural vector autoregression (SVAR) framework proposed by Blanchard and Perotti (2005), further augmented to allow for the possibility that taxes, spending and interest rates might respond to the level of the debt over time. We examine the dynamic responses of output, inflation and the interest rate to changes in government spending and revenues and analyse the contribution of shocks to New Zealand's business cycle for the period 1983:1-2010:2. We find that the effects of government expenditure shocks in New Zealand appear to be positive but small in the short-run at the cost of higher interest rates and lower output in the medium to long-run. The sign of the effects of tax policy changes are less clear cut, but again the effects on GDP appear similarly modest. Past fiscal policy is analysed through a historical decomposition of the shocks in the model. This suggests that discretionary fiscal policy has had a generally pro-cyclical impact on GDP over the last fifteen years, and a material impact on the real long-term interest rate. A fiscal expansion has a positive but limited impact on inflation.
Keywords: C32; E32; E62; 330; Fiscal policy; business cycle fluctuations; vector autoregression; debt feedback; Finanzpolitik; Wirkungsanalyse; Zeitreihenanalyse; Neuseeland